THE DESIGN OF BANYUMAS REGIONAL PUBLIC HOSPITAL AT BANYUMAS DISTRICT - Andreas, Yehezkiel
The Banyumas Hospital Mental Health Service Installation was appointed by the Ministry of Health and the Banyumas Regional Government as a national pilot project for mental health services at General Hospitals. But in reality, the installation conditions are still less than ideal. So, it needs to be designed to comply with applicable standards. This final project aims to design a foundation system that is able to carry the structural load based on the design results and a retaining wall that keeps the slopes level during the excavation process for the basement. The pile foundation system is designed with a diameter of 60 centimeters and a tip depth of 27 meters. Analysis of the axial bearing capacity of single pile and group pile, analysis of the lateral bearing capacity of single pile with the help of LPILE software, analysis of the lateral bearing capacity of group pile with the help of GROUP software, analysis of settlement and difference in foundation settlement, and design of the sloof or tie beam should be done when designing the foundation. The results of the pile configuration design consist of 11 types of pile groups with different lengths and widths of pile caps but with the same height of 90 cm. The basement at Banyumas Hospital consists of 2 basement floors with a depth of each floor at an elevation of 3.5 meters and 7 meters below ground level, with a total excavation of up to 8 meters, so a basement wall with a diaphragm wall type plus strut reinforcement is needed. Analysis of the excavation and basement walls was carried out using PLAXIS 2D software with a hardening soil model. The results of the analysis show that a diaphragm wall with a wall depth of 16 meters and a wall thickness of 60 centimeters is needed to accommodate basement requirements and meet stability and deformation requirements, and steel strut reinforcement with an IWF 400.400.13.21 profile is needed. During the excavation, dewatering is designed through six points with a total discharge of 420 liters per minute.